Factors Affecting Employee Performance in the Village Office of South Seluma Subdistrict - Suryati, Suryati; Angriani, Ida; Rahman, Abdul (Jurnal Fokus Manajemen, 2025)
The purpose of this study was to determine the Factors Affecting Employee Performance at the Village Office of Seluma Selatan District. The sample in this study was 72 village office employees in Seluma Selatan District. Data collection using questionnaires and the analysis methods used were multiple linear regression, determination test and hypothesis test. The results of the regression analysis showed Y = 4.362 + 0.193X1 + 0.367 X2 + 0.361X3 + e. This illustrates a positive regression direction, meaning that there is a positive influence between X1 (motivation), X2 (education) and X3 (work discipline) on performance (Y). This means that if the variables of motivation, education and work discipline increase, it will increase the performance of the newspaper. The coefficient of determination is 0.584. This means that X1 (motivation), X2 (education) and X3 (work discipline) have an effect on performance (Y) of 58.4% while the remaining 41.6% is influenced by other variables not examined in this study. The results of the t-test at a significance level of 0.05 explain that partially (individually) the variables of education, motivation and work discipline have a significant effect on the newspaper performance variable because the significant value is smaller than 0.05. The results of the F-test at a significance level of 0.05 explain that the variables of education, motivation and work discipline have a simultaneous (together) effect on the performance of Village Office Employees because the significant value is smaller than 0.05